Pemanfaatan Teknologi Digital Dalam Meningkatkan Literasi Mahasiswa - Delvin Krisnawati Lahagu; Teti Septiani Lahagu (CV. SINAR HOWUHOWU, 2024)
In today's digital age, the use of technology plays an important role in improving student literacy. Digital literacy, which includes the ability to access, evaluate and utilize information from digital sources, is a key skill for students to succeed in both educational and professional settings. This research explores various aspects of the use of digital technology in education and its impact on improving student literacy. Through online learning platforms such as YouTube and Google Classroom, students can access materials in flexible ways, collaborate with peers and interact with lecturers, creating a more dynamic and interactive learning experience, which in turn increases their motivation and participation in the learning process. Improving digital literacy requires a more structured approach, such as training and educational programs designed to help individuals understand and utilize technology more effectively. Therefore, digital literacy is not only about technical skills, but also about understanding the context and the ability to perform constructive social actions. In conclusion, the utilization of digital technology in education is essential to improve students' literacy, prepare them for the challenges of an increasingly complex world, and ensure they can adapt to the demands of a digital world.